Dampak Perkembangan Teknologi Terhadap Mata Pencaharian Masyarakat - asyifah, Salsabila Rahmania; Faristiana, Andhita Risko (Universitas Gajah Putih, 2024)
In our lives at this time of course we will not be separated by technology. Because it is an effort for humans to meet the needs of their lives both in terms of quality and quantity. Technology has many impacts on human life, both negative and positive impacts. This research was conducted in Dolopo Village, Dolopo District, Madiun regency, East Java province. The formulation of the problems that will be discussed in this study include: 1) the response of the Dolopo community to the entry of technology into people’s livelihoods. 2) on the impact of the use of technology on the socio-economic community in Dolopo Village. The type of research used is field research, while data collection techniques are carried out by observation, and interviews. The results of this study concluded that the impact of technological developments facilitate human activities but on the other hand also lead to loss of community livelihoods.